2018
DOI: 10.20471/acc.2018.57.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Healthcare Quality – Paradigm of MEDQUAL

Abstract: SUMMARY – Medical activity is assumed to be service activity the effects of which can be measured. The SERVQUAL scale was used as a starting point for our research, which resulted in a new, adopted scale called MEDQUAL. The MEDQUAL scale aims to measure the quality of healthcare provided by medical staff of one hospital department instead of the overall quality of hospital services or parts of services on which medical staff in one department has no influence. The study was conducted in a clinical hospital dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…in conducting an extensive literature review, Castle et al 17 examined 59 studies providing information on 54 instruments used for researching hospital patient perceptions of healthcare; they have concluded that despite a diversity of research instruments, the salience of use of survey instruments has increased. Although there are research studies (e.g., Shemwell and yavas 18 , musa-Juroš et al 19 ) where the authors tried to propose and test a scientifically based model and/or an appropriate scale to measure the specific quality of hospital healthcare services, a unique method and instrument have not yet been developed.…”
Section: Approaches and Methods For Service Quality Measurement In Homentioning
confidence: 99%
“…in conducting an extensive literature review, Castle et al 17 examined 59 studies providing information on 54 instruments used for researching hospital patient perceptions of healthcare; they have concluded that despite a diversity of research instruments, the salience of use of survey instruments has increased. Although there are research studies (e.g., Shemwell and yavas 18 , musa-Juroš et al 19 ) where the authors tried to propose and test a scientifically based model and/or an appropriate scale to measure the specific quality of hospital healthcare services, a unique method and instrument have not yet been developed.…”
Section: Approaches and Methods For Service Quality Measurement In Homentioning
confidence: 99%
“…Results revealed that the tangible element of the SERVQUAL scale is ranked highest, while reliability is viewed as the most important factor for the outpatients' satisfaction. Collecting data from 300 respondents (169 patients and 131 medical staff members) in the department of clinical hospitals in Croatia, Musa-Juroš et al (2018) designed a new MEDQUAL scale by expanding the SERVQUAL model to measure patient satisfaction with the quality of healthcare received and satisfaction of medical staff with the quality of healthcare provided. The results showed that the professionalism of the medical staff (patients' perspective) and improvements in the quality of medical services (medical staff perspective) have a significant influence on patient satisfaction and medical staff, respectively.…”
Section: Background Theoretical Backgroundmentioning
confidence: 99%
“…The Nordic view led by Gronroos (1984) differentiates service quality on two measurements as utilitarian and specialised quality, whereas the American school view led by Parasuraman, Zeithaml, and Berry (1985) builds the service quality model SERVQUAL with five dimensions to include tangibles, empathy, responsiveness, assurance, and reliability. For the health industry, the MEDQUAL scale was developed by Musa-Juroš et al, (2018) which included three dimensions: trust in the doctor, professionalism, and the organisation of the department, and the model resulting drawbacks like low specificity, usable for one single department, and the need to collect data at equal time intervals. Lee (2017) proposed HEALTHQUAL, an integrated model to measure medical and health care service quality, which uses mixed dimensions from the Institute of Medicine, SERVQUAL, a mixed SERVQUAL model, and measurement criteria of international accreditation institutions.…”
Section: Service Qualitymentioning
confidence: 99%
“…According to the scales adopted for the study, a quantitative survey questionnaire with 30 items was designed. The service quality related items were adapted from the work of Lee (2017), Chaterjee et al, (2018), andMusa-Juroš et al, (2018). The items for customer satisfaction were adapted from Chaterjee et al, (2018).…”
Section: Measures For This Studymentioning
confidence: 99%